Management affects the diversity and functions of root and leaf-associated microbiomes: implications for olive resilience - Fosso, Emanuele; Gizzi, Gina; Tartaglia, Maria; Prigioniero, Antonello; Ranauda, Maria Antonietta; Maisto, Maria; Labella-Ortega, Mónica; Zuzolo, Daniela; Guarino, Carmine (Frontiers in Plant Science, 2026)
This study explores the impact of organic, conventional, and traditional agricultural management on the aboveground and belowground microbiomes of Olea europaea L. cv. Ortice, a cultivar widely cultivated in southern Italy’s agricultural landscape. Through metabarcoding analyses (16S rRNA and ITS), we assessed the influence of farming approaches on the microbiome traits of the olive holobiont. Our findings demonstrate that agricultural management practices significantly shape microbiome composition both aboveground and belowground. The conventional management was associated with the highest number of microbial biomarkers aboveground, mainly belonging to Rhizobiaceae and Rhodocyclaceae families. Instead, Fusarium (family Nectriaceae) was the most abundant taxon under organic treatment. Regarding root-associated microbiome, organic management supported a greater number of microbial biomarkers, including the bacterial genera Actinophytocola and Streptomyces, both known for their roles in promoting plant health and protecting against pathogens. In traditional systems, biomarkers included taxa from the order Burkholderiales and the species Nocardioides islandensis. Functional analysis of the aboveground fungal community revealed a higher capacity for endophytic interactions in traditional management, predominantly involving known pathogenic species such as Alternaria alternata, Aureobasidium spp., and Cladosporium spp. Similarly, traditional management was associated with significant enrichment of phototrophic functions belowground, mainly attributed to the bacterium Rhodopseudomonas palustris. Conversely, the potential for endophytic interactions was significantly greater under conventional management and was primarily linked to fungi within the class Sordariomycetes. Management practices shape distinct microbial communities both aboveground and belowground of olive groves, potentially influencing the resilience of Mediterranean agroecosystems and underscoring the importance of sustainable strategies.